Formation of Research Competence in Teaching Biology at a Comprehensive School - Qarakhanova Lobarhon Musakhonovna (Genius Journals, 2023)
The article discusses the main conditions for the formation of research competence in the section of school biology. The authors proved the effectiveness of the created methodology, the use of which improves the quality of students' knowledge and the level of assimilation of biological concepts, phenomena and processes.
Keywords: teaching biology; competence